Loose Polyester Nanofiltration Membrane Designed with Hydroxyl-Ammonium for Efficient Dye/Salt Separation - Nan Ma; Guiliang Li; Yang Liu; Shenghua Zhou; Fu Liu (Membranes, 2025)
Efficient dye/salt separation poses a great challenge to nanofiltration (NF) membrane technology in the desalting sector of the dye synthesis industry. In this study, we fabricated a novel loose polyester NF membrane via an interfacial polymerization method using “hydroxyl-ammonium” biquaternary diethanolamine (MDET) and trimesoyl chloride. The molecular design of MDET provides a loose crosslinking network, showing high rejection of dyes and the passage of monovalent salt/divalent salt ions in the dye solution, exhibiting exceptional filtration efficiency with high selectivity. Furthermore, the membrane exhibits excellent operational stability for over 100 h, demonstrating superior antifouling properties and high resistance to chlorine. This study provides new insights into the role of dyes and mono- and divalent ions in desalination processes related to the dye synthesis industry.